Changing Face of Science Education in India During the COVID-19 Pandemic - Singh, Sunita; Verma, Kajal (JOURNAL OF INDIAN EDUCATION, 2021)
COVID-19 pandemic has led educational institutions to be shut down to contain the infection. Still, it was carried out online, which resulted in the students’ isolation from physical interaction in contrast to the exploratory nature of Science. As a result, it compelled researchers to investigate the nature of science education during COVID-19. This paper critically analyses the nature of science education in Indian classrooms in a complete virtual mode. The exploratory method was adopted where teachers, students, and parents were interviewed through zoom meetings, and for further information, semi-structured questionnaires in the form of Google forms were shared. The study has been conducted from August to October 2020. The findings reveal that online mode was not favourable for many learners, due to lack of resources and facilities. Responses confirm that it was inadequate to facilitate science teaching and learning in a complete virtual mode as it limits the basic premise of nature of science, i.e., exploration. Students weren’t able to perform experiments at home and teachers were not techno-savvy. However, they still managed to teach science at the elementary level, subsequently, a daunting task at secondary and senior secondary level.